Biringan: A Folktale of the Invisible City of Samar - Poe, Maria Leonora; MACAPUGAS, LARRY; DELACRUZ, JULITA; Daguinod, Mario (International Journal of Language and Literary Studies, 2025)
This study explores the folktale of Biringan City, an invisible and mythical metropolis in Samar, Philippines, believed to be inhabited by enchanted beings known as engkantos. Despite advances in science and technology, certain phenomena like Biringan remain unexplained and persist through oral tradition as folklore. Using a qualitative approach with thematic analysis, data were collected from in-depth interviews with ten local participants aged 50 and above from Pagsanjan, Samar. The study uncovered four main themes characterizing Biringan City: (1) a Perfect Dwelling Place featuring advanced technology, overwhelming wealth, beautiful environment, and friendly inhabitants; (2) Deception, where the city’s allure is used to trap visitors through enticing but dangerous offers such as eating black rice or accepting healing powers at a high cost; (3) Protection, including beliefs that the city shields locals from harm such as zero COVID-19 casualties and avoidance of conflict; and (4) Healing, involving mystical powers to cure diseases and even raise the dead. The folktale reflects a rich cultural narrative that blends wonder, caution, and mystery, illustrating how local communities interpret and preserve their heritage through storytelling. This research adds depth to existing accounts of Biringan, highlighting its significance in Philippine folklore and cultural identity.